Understanding and conducting information systems auditing - Hingarh, Veena; Ahmed, Arif (Accountant). (Hoboken, N.J ; Chichester : Wiley, 2013)
A comprehensive guide to understanding and auditing modern information systems The increased dependence on information system resources for performing key activities within organizations has made system audits essential for ensuring the confidentiality, integrity, and availability of information system resources.
Conducting an information systems audit. Overview of systems audit ; Hardware security issues ; Software security issues ; Information systems audit requirements ; Conducting an information systems audit ; Risk-based audit ; Business continuity and disaster recovery plan ; Auditing in the e-commerce environment ; Security testing ; Case study: conducting an information systems audit -- Information systems auditing checklists. ISecGrade auditing framework ; ISecGrade checklists ; Session quiz.
Includes index.
Keywords: Information resources management; Information resources -- Auditing